Patients' Willingness to Share Limited Endoscopic Resources: A Brief Report on the Results of a Large Regional Survey. Issue 2 (September 2021) - Piper, Marc S.; Zikmund-Fisher, Brian J.; Maratt, Jennifer K.; Kurlander, Jacob; Metko, Valbona; Waljee, Akbar K.; Saini, Sameer D.
Background. In some health care systems, patients face long wait times for screening colonoscopy. We sought to assess whether patients at low risk for colorectal cancer (CRC) would be willing to delay their own colonoscopy so higher-risk peers could undergo colonoscopy sooner.Methods. We surveyed 1054 Veterans regarding their attitudes toward repeat colonoscopy and risk-based prioritization. We used multivariable regression to identify patient factors associated with willingness to delay screening for a higher-risk peer.Results. Despite a physician recommendation to stop screening, 29% of respondents reported being "not at all likely" to stop. However, 94% reported that they would be willing to delay their own colonoscopy for a higher-risk peer. Greater trust in physician and greater health literacy were positively associated with willingness to wait, while greater perceived threat of CRC and Black or Latino race/ethnicity were negatively associated with willingness to wait.Conclusion. Despite high enthusiasm for repeat screening, patients were willing to delay their own colonoscopy for higher-risk peers. Appealing to altruism could be effective when utilizing scarce resources.